1997
DOI: 10.1111/j.1751-1097.1997.tb08579.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Efficacy Analysis of the Phototherapeutic Lutetium Texaphyrin (PCI‐0123) in the Murine EMT6 Sarcoma Model

Abstract: Lutetium texaphyrin (PCI-0123) is a pure, water-soluble photodynamic therapy (PDT) agent that is activated by tissue-penetrating far red light. The sensitizer is highly fluorescent and exhibits a strong, broad emission signal at 750 nm. In vitro cellular uptake studies revealed an increase in sensitizer retention with incubation time. Confocal laser scanning microscopy demonstrated that the intracellular localization site of PCI-0123 is the lysosomes. Ensuing illumination of the EMT6 cells led to lysosomal bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 13 publications
(21 reference statements)
7
62
1
Order By: Relevance
“…MLu (Pharmacyclics, Inc., Sunnyvale, CA) injection was administered intravenously (0.5-2 mg/kg) 3-24 h before light administration (16,24). After the patient was anesthetized, the interstitial CDF were placed in the gland using a template with evenly spaced holes, which was attached to the TRUS unit.…”
Section: Pdt and In Vivo Light Measurementsmentioning
confidence: 99%
“…MLu (Pharmacyclics, Inc., Sunnyvale, CA) injection was administered intravenously (0.5-2 mg/kg) 3-24 h before light administration (16,24). After the patient was anesthetized, the interstitial CDF were placed in the gland using a template with evenly spaced holes, which was attached to the TRUS unit.…”
Section: Pdt and In Vivo Light Measurementsmentioning
confidence: 99%
“…The present study is limited to four compounds: sulfonated chloro-aluminum phthalocyanine (AlPcS n ) [14], benzoporphyrin derivative monoacid ring A (BPD-MA) [15,16], lutetium texaphyrin (Lutex) [17][18][19], and aminolevulinic acid (ALA), a precursor of the endogenous sensitizer protoporphyrin IX (PpIX) [20]. In Table 1 Thursday we present some published results of the PDT efficiency, relative to Photofrin, of these selected sensitizers [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…32 The PS lutetium texaphyrin also accumulates preferentially in lysosomes in EMT6 murine mammary sarcoma cells. 33 Intracellular tracking of Photofrin and N-monoaspartyl chlorin e6 has revealed that the former enters the cell by diffusion and localizes in mitochondria, while the latter is endocytosed and then localized in lysosomes. 20 Incubation of bladder carcinoma cells with chlorin e6 leads to localization of the latter in the plasma membrane and other peripheral cell membranes, 34 whereas lysyl chlorin p6 is largely found in endosomes.…”
Section: Subcellular Distribution Of Photosensitizers In Vitromentioning
confidence: 99%